Experiment-Based Fatigue Behaviors and Damage Detection Study of Headed Shear Studs in Steel–Concrete Composite Beams - Xu, Jun; Sun, Huahuai; Chen, Weizhen; Guo, Xuan (Applied sciences, 2021)
Many in-service bridges with steel–concrete composite beams are currently aging and experiencing performance deterioration. Under long-term cyclic loads from traffic on bridges, headed shear studs in steel–concrete composite beams are vulnerable to fatigue damage. The comprehensive understanding of fatigue behaviors and the feasible detection of fatigue damage of headed shear studs is, thus, crucial for the accurate numerical simulation of the fatigue crack propagation process. The paper, thus, experimentally investigates the fatigue behaviors of headed shear studs through push-out tests of three specimens. The fatigue failure modes and cyclic strain evolution of specimens are analyzed. The fatigue lives of headed shear studs are compared with the S–N curves of the AASHTO, Eurocode 4 and BS5400 codes. The fatigue crack details of shear studs in push-out tests are then detected using the ultrasonic non-destructive testing. The results show that the root fracture is the main fatigue failure mode of shear studs under fatigue loading. The fatigue life estimations based on the three current codes (i.e., AASHTO, Eurocode 4 and BS5400) can be safely guaranteed only with different safety redundancies. The strain at the shear stud with fatigue damage shows a consistent increasing trend followed by decreasing behavior after reaching the peak value with the loading cycles. Moreover, the feasibility of the ultrasonic non-destructive testing with the combination of a strain measurement for fatigue crack details detection of headed shear studs in composite beams is proved.